Effect of polarization adjustment towards the performance of SOA-based multiwavelength fiber laser - Muridan N.; Sulaiman A.H.; Abdullah F.; Yusoff N.M. (Elsevier GmbH, 2023)
Fiber amplifiers; Fiber lasers; Light polarization; Optical switches; Polarization-maintaining fiber; Angle settings; Half-wave plates; Lyot filters; Multi-wavelengths; Multiwavelength fiber laser; Nonlinear polarization rotation; Optical-; Performance; Plate waves; Quarter wave-plate; Semiconductor optical amplifiers